Impact of fishing activities on the fisheries resources and Manado Bay Aquatic environment - Sumampouw, Trine; Reppie, Emil; Lasut, Markus T (AQUATIC SCIENCE & MANAGEMENT, 2014)
Manado Bay waters have long been known as a center of artisanal fisheries activities because of the availability of abundant fisheries resources. However,  continuous increase in technoligcal  development and fish resources demand make natural resources exploitation tend to destruct the  aquatic habitat and fish resources itself. Therefore, this study was aimed to inventory the types of fishing gears operated in Manado Bay; evaluate the possible impact on fish resources and environment; and analyze the status of fishing fisheries sustainability. This study was based on survey methods, through direct observation of fishing process and observations on the catch composition. Fisheries sustainability status was analyzed using Rapfish program. Common fishing gears used by fishermen in Manado Bay were multi hooks vertical hand line (noru), bottom hand line, trolling line, bottom long line, surface gill net, bottom gill net and traps. Fishing gears that do not have an impact on fish resources and environment is noru fishing, trolling and surface gill net, while bottom long line, bottom gill net and trap could potentially have negative impact on fish resources and physical seabed habitat. ordination sustainability status analysis of fishing fisheries in Manado Bay for each dimension is still considered as sustainable enough. Perairan Teluk Manado telah lama dikenal sebagai pusat aktivitas perikanan rakyat karena ketersediaan sumber daya ikan masih melimpah. Tetapi perkembangan teknologi dan permintaan sumber daya ikan yang terus meningkat menyebabkan pengeksploitasian sumber daya alam cenderung merusak habitat perairan dan sumber daya ikan itu sendiri. Oleh karena itu penelitian ini bertujuan untuk menginventarisir jenis-jenis alat tangkap yang dioperasikan di perairan Teluk Manado, mengevaluasi kemungkinan dampak alat tangkap terhadap sumber daya ikan dan lingkungan, dan menganalisis status keberlanjutan perikanan tangkap. Penelitian ini didasarkan pada metode survei, melalui pengamatan langsung terhadap proses penangkapan ikan dan mengamati keragaman komposisi hasil tangkapan. Status keberlanjutan perikanan dianalisis dengan program Rapfish. Alat tangkap yang umum digunakan oleh nelayan di perairan Teluk Manado terdiri dari yaitu pancing noru, pancing dasar, pancing tonda,  rawai dasar,  soma landra pajeko, soma landra rakit,  jaring insang dasar dan bubu. Alat tangkap yang tidak memberikan dampak terhadap sumber daya ikan dan lingkungan adalah pancing noru, pancing tonda, soma landra pajeko dan soma landra rakit. Sedangkan alat tangkap yang berpotensi memberikan dampak pada sumber daya ikan dan kerusakan fisik habitat dasar perairan adalah pancing dasar, rawai dasar, jaring insang dasar dan bubu. Hasil ordinasi status keberlanjutan perikanan tangkap di Teluk Manado yang dianalisis pada masing-masing dimensi masih tergolong cukup berkelanjutan.